Influence of Zn in the CdS Crystal Lattice and Its Impact over the Catalytic Activity in the H2 Production - Luis Fernando Morelos-Medina; Rufino Nava-Mendoza; Carlos Martín Cortés-Romero; Rodrigo Rafael Velázquez-Castillo; J. Santos-Cruz; María de los Ángeles Cuán-Hernandez (Journal of Chemistry)
Solid solutions ZnxCd1−xS were compared by coprecipitation and sonochemistry methods, where x=0.2. This rate is the one that presents the best photocatalytic activity and the best performance for the production of hydrogen from a water source, according to our previous results. The influence of the synthesis method on the morphology and its electronic properties of the CdS and Zn0.2Cd0.8S systems was investigated, as well as the effect of the incorporation of Zn in the crystal lattice and its effect on the production of hydrogen from the division of water. X-ray diffraction characterization confirmed the formation of a solid solution corresponding to a face-centered cubic crystalline phase with preferential growth of (111), (220), and (311) planes and hierarchical morphology according to SEM and TEM microscopy, formed by aggregated nanoparticles of ZnxCd1−xS compound. The crystallite size decreased with the Zn incorporation in the crystal lattice from 8.61 nm by a coprecipitation method to 4.37 nm when the synthesis was assisted with sonochemistry, and the crystallite sizes range from 7.92 nm to 3.80 nm for the case of CdS pure. Other characterization techniques were also used, such as photoluminescence (PL), Raman microscopy, and N2 adsorption and desorption. The PL results show tunability of band edge emission as a function of zinc concentration in the Zn0.2Cd0.8S nanoparticles. For the water splitting to hydrogen production, the separation of the charge carriers promoted by the incorporation of Zn in addition to the shallow trap emissions generated defects in the catalyst structure; such processes are important factors found which increased with the sonochemical method, as well as the potential matched positions.